TEKNIK KEAMANAN JARINGAN DAN DATA DENGAN LINUX DEMILITARIZED ZONE - Jufriadif Naam (Jurnal PROCESSOR, 2012)
In a computer network, must have its own security. It acts to protect the data that isconsidered imPortant, because to be closed and confidential. Topology, a goodplacement strategy and a clear calculation can provide added value to data securityand server. Linux is touted to have all the above criteria. In addition to the level ofstability and the ease and consider things in Linux because it is opensource. In aforeign country. It's not taboo anymore to use Linux as their data centers. Because inaddition to safety, service is also easy. Therefore Linux precedence over the priorityto build a server.